Synthesis, characterization and evaluation biological activity of some 2-mercaptobinzemidazol complexes - Anfal Salam Al-Mahdawi; Noor Sabah Al-Obaidi; Amna Ali Ahmad; Tabarak Ali Jumaa; Zahraa Ali Abas; Haider Salah Mahdi (Results in Chemistry)
This study involved prepare new four complexes of 2-mercaptobenzomidazole with the metals (Cu, Zn, Cd, and Pb). The synthesized complexes were characterize by measuring ultraviolet spectroscopy, the wave length (λ nm) (318, 333.4) of ligand (272, 296.2, 624.8), (254, 306), (257, 311) and (262, 314) of synthesized complexes respectively, then by infrared spectroscopy (FTIR) the results of the infrared spectroscopic examination showed the shifted in the absorption bands of (S-H) and (N-H) groups of the ligand as a result of coordination, molar conductivity, atomic absorption (AAS) spectroscopy and ratio of elements (CHNS) to determine the formulas of the complexes, the complexes shown a distorted octahedral crystal structure, and the molecular formula of the complexes was [M (C7H6N2S)2Cl2]. The synthesized complexes were assessed for their biological activity against different four types of bacteria (Staphylococcus aureus, Escherichia coli, spherical bacteria, Staphylococcus epidermidis, and Klebsiella pneumoniae), in addition to a type of Fungus, Candida albicans, the comparison include the activity of the complexes in relation to the antibiotic penicillin and the activity of 2-mercaptobenzomidazole, the prepared complexes had the highest biological activity compared to ligand and the antibiotic penicillin, the best prepared complex was the cadmium complex, the diameter of inhibition ranged between (27–36 nm) against bacteria and (40 nm) against the fungus, the complexes can be suggested as a more activity antibiotic than ligand and penicillin.